La via per l’Inferno. Una possibile genealogia figurativa per un film italiano del 1911 - Galluzzi, Francesco (Opus Incertum, 2021)
The 1911 Italian film Inferno (directed by Francesco Bertolini, Giuseppe De Liguoro and Adolfo Padovan) lies at the intersection between the new art of cinema, cultural memories and the horrific and marvellous elements of the 18th century tradition of the Sublime, between high and low cultural references. This text attempts to retrace the course of the artistic events that allowed this crossing to be possible.